The Perceptions of Thai EFL Students towards English Linguistic Imperialism in Facebook Context - Kong-in, Wapee (Language and Linguistics, 2018)
This research aimed to investigate Thai EFL students’ perception towards English linguistic imperialism in the context of Facebook network. Language exposure on social network was the variable to be analyzed. Questionnaire was used to collect data from 142 participants majoring in English. The findings showed intrinsic argument, according to linguistic imperialism theory, correlated with language exposure significantly (r = - .178, p = .035). It was also dependent on degrees of English use frequency. In-depth interview uncovered eleven reasons to support Thai EFL students’ mutual communication in English on Facebook i.e. restriction of conversation group, prestige, cliché, special occasion, practicing English skills, affective conveyance, sharing resource, conveniences, modernity and exceptionality, familiar phatic function, and solidarity. การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาการรับรู้จักรวรรดินิยมทางภาษาอังกฤษของนักศึกษาไทยที่เรียนภาษาอังกฤษในฐานะภาษาต่างประเทศในบริบทของ Facebook โดยพิจารณาตัวแปรในด้านประสบการณ์ใน การใช้ภาษา เก็บข้อมูลจากนักศึกษาสาขาวิชาภาษาอังกฤษ จำนวน 142 คน ผลการวิจัยพบว่าประเด็นปัจจัยภายใน (Intrinsic Argument) ตามทฤษฎีจักรวรรดินิยมทางภาษา มีความสัมพันธ์กับประสบการณ์ทางภาษาอย่างมีนัยสำคัญทางสถิติ (r = - .178, p = .035) ทั้งนี้ ขึ้นอยู่กับระดับความถี่ในการใช้ภาษาอังกฤษ ผลจากการสัมภาษณ์เชิงลึกพบว่าเหตุผลในการใช้ภาษาอังกฤษในบริบทเครือข่ายทางสังคมประกอบด้วย 11 ข้อ ได้แก่ (1) การจำกัด วงสนทนา (2) เกียรติภูมิ (3) คาติดปาก (4) โอกาสพิเศษ (5) การฝึกฝนภาษาอังกฤษ (6) การสื่อความหมายเชิงทัศนคติ/อารมณ์เฉพาะ (7) การแบ่งปันทรัพยากร (8) ความสะดวก (9) ความทันสมัยและความเฉพาะตัว (10) การสื่อสัมพันธภาพทางสังคมที่คุ้นชิน และ (11) ความเป็นปึกแผ่นเดียวกัน